Analisis Kebijakan Sekolah Dalam Peningkatan Profesionalisme Guru Di Kecamatan Kambera - Ambu, Anestasia Ata; Nurjaman, Asep (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: Professional teachers can move the dynamics of the progress of national education, for that a continuous, targeted and effective development process is needed. The process to improve professional teachers needs to support all elements related to the teacher. This study aims to describe 1) school policy in increasing teacher professionalism in the Senior/Vocational High School Kambera District. 2) Efforts to the obstacles faced in the implementation of increasing teacher professionalism in the Senior/Vocational High SchoolKambera District. This study used a qualitative descriptive approach with data collection methods in the form of observation, interviews, and study of documents that are used as sources of primary data and secondary data. The location of this study was at Senior High School 1 Kambera, Payeti Christian Senior High School, and Vocational High School Negeri 5 Waingapu. The results showed that: 1) the implementation of MGMP activities, PKB, Diklat, curriculum development from the three schools was still lacking because not all teachers were sent in these activities. The obstacles faced are continuing professional development, namely the lack of teacher's understanding of teaching materials, and the lack of opportunities to attend training as a support to become professional teachers. 2) Efforts towards the obstacles faced in implementing teacher professionalism have been carried out related to the implementation of PKB, MGMP, curriculum development, training at the school, regional and provincial levels, but these achievements have not been fully maximized.Keywords: School Policy, Professionalism, TeachersÂ Abstrak: Guru profesional dapat menggerakkan dinamika kemajuan pendidikan nasional, untuk itu diperlukan suatu proses pembinaan berkesinambungan, tepat sasaran dan efektif. Proses untuk meningkatkan guru profesional perlu dukungan semua unsur yang terkait dengan guru. Penelitian ini bertujuan untuk mendeskripsikan 1) kebijakan sekolah dalam peningkatan profesionalisme guru di SMA/SMK Kecamatan Kambera. 2) Upaya terhadap kendala yang dihadapi dalam pelaksanaan peningkatan profesionalisme guru di SMA/SMK Kecamatan Kambera. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan metode pengumpulan data berupa obsevasi, wawancara, dan studi dokumen yang dijadikan sebagai sumber data primer dan data sekunder. Lokasi penelitian ini di SMA Negeri 1 Kambera, SMA Kristen Payeti, dan SMK Negeri 5 Waingapu. Hasil penelitian menunjukkan bahwa: 1) pelaksanaan kegiatan MGMP, PKB, Diklat, pengembangan kurikulum dari ketiga sekolah tersebut masih kurang, karena tidak semua guru-guru dikirim dalam kegiatan-kegiatan tersebut. Adanya kendala yang dihadapi yaitu pengembangan keprofesionalan secara berkelanjutan yaitu kurangnya pemahaman guru terhadap materi ajar, dan kurangnya kesempatan untuk mengikuti pelatihan-pelatihan sebagai penunjang menjadi guru profesional. 2) Upaya terhadap kendala yang dihadapi dalam pelaksanaan peningkatan profesionalisme guru sudah dilaksanakan terkait pelaksanaan PKB, MGMP, pengembangan kurikulum, diklat pada tingkat sekolah, daerah, maupun provinsi tetapi pencapaian tersebut belum sepenuhnya maksimal.Kata kunci: Kebijakan Sekolah, Profesionalisme, Guru